Optimierung von Verfahren zur Lösung rechtsrelevanter Wissensprobleme in kritischen Infrastrukturen : Befunde im Smart Grid und technikrechtliche Empfehlungen - Lorenz, Mieke (Schriften des Zentrums für Angewandte Rechtswissenschaft / ZAR, Zentrum für Angewandte Rechtswissenschaft, Karlsruher Institut für Technologie, 2018)
This work is concerned with regulation and the reconciliation of interests at the interface of energy sector and privacy law. To improve regulatory knowledge within the Smart Grid, an existing procedure of the Federal Network Agency is proposed. By enriching this procedure through aspects of data protection compliant technical engineering and elements of visualisation - drawn from construction and planning law - it is also possible to reduce the complexity of regulatory knowledge generation.